Hubungan Usia, Pendidikan dan Paritas Dengan Kelengkapan Pelayanan Antenatal Care Pada Ibu Hamil di Puskesmas Sukarami Kecamatan Sungai Rotan Kabupaten Muara Enim Tahun - Sari, Novita; Chairuna, Chairuna; Riski, Merisa (NHM PRESS, 2024)
Maternal mortality rates (MMR) are still very high, around 810 women die from complications related to pregnancy or childbirth worldwide every day, and around 295,000 women die during and after pregnancy and childbirth. Efforts to accelerate the reduction of the Maternal Mortality Rate (MMR) are carried out by ensuring that every mother is able to access quality maternal health services. The importance of ANC (Antenatal Care) visits has not been a top priority for some pregnant women regarding their pregnancies in Indonesia. The purpose of this study was to determine the relationship between age, education and parity simultaneously with the completeness of antenatal care services for pregnant women at the Sukarami Health Center, Sungai Rotan. The research design used an analytical survey with a cross sectional approach. The population in this study were third trimester pregnant women (gestational age more than 28 - 40 weeks) who came to check their pregnancies at the Sukarami Health Center, Sungai Rotan District, Muara Enim Regency from January to December 2022, totaling 86 people. The sampling technique in this study was carried out by means of total sampling with a total sample of 86 respondents. Data collection uses a checklist sheet. Data analysis used univariate analysis and bivariate analysis using the chi square test. The results of the study show that there is a relationship between age (p value = 0.037), education (p value = 0.011) and parity (p value = 0.026) with the completeness of antenatal care services for pregnant women at the Sukarami Community Health Center, Sungai Rotan District, Muara Enim Regency in 2023. It is hoped that the results This research can be used as evaluation material to increase the number of prenatal checks such as by conducting counseling or counseling to pregnant women regarding prenatal checks.